Performing Anathema: Reading ἀνάθεμα ἔστω (Galatians 1:8–9) as Speech-Act and Ritual with the Apostle Paul and the Fourth- and Fifth-Century Church Fathers - Bay, Carson (Religion in the Roman empire, 2022)
In one of his earliest letters, the Apostle Paul twice places a curse upon anyone who does or who might proclaim a gospel to the Galatian church different from he and his comrades had preached (Galatians 1:8-9). This curse took an unprecedented verbal formula: ἀνάθεμα ἔστω. This article argues that, in its original context, this curse should be read as an intended (and apparently effective) speech-act ritual, a component of establishing authority and drawing boundary lines within the nascent Church. It then shows that, by the time this formula is picked up later in Greek by fourth- and fifth-century Christian bishops, it has lost much of its original meaning, and perhaps some of its force. In late antiquity, proclaiming ἀνάθεμα was no longer a 'magical' speech-act, a singular event of a given church's community ritual, but an increasingly common and institutionalised way of contesting and codifying borders within an ecclesial, theological, and legal superstructure much developed and much changed.